The Political Economy of Environmental Goods and Services: An Economic Nationalist Perspective - Ugalde Hernández, Oscar (2025)
Since the launch of the Doha Development Round in 2001 and its subsequent Ministerial Declaration, the call has been made to member countries of the World Trade Organization (WTO) to develop negotiations to reduce or eliminate tariff and non-tariff barriers to environmental goods and services. However, multilateral consensus between countries has been very complex to achieve. Developing countries have interests that are cornerstones of their representations’ participation in the multilateral and plurilateral negotiations before the WTO. These countries justify their interests with arguments based on economic nationalism. Therefore, this research aims to answer the following research questions: Although countries are aware of the importance of liberalizing BSA trade in multi-level trade negotiations, states have been tempted to influence and intervene in their domestic economies and other nations’ economies on behalf of their interests. As a method, a comparative analysis will be conducted between developing countries’ commercial positions/interests vis-à-vis developed countries, supported by an exhaustive literary review of the various protectionist arguments used to justify their position of economic nationalism. The a priori expectation of the results developed in this research is that the various multilateral negotiations on trade in environmental goods and services have not considered the developing countries’ positions/ interests. Therefore, proposals at the multilateral and plurilateral levels do not represent these countries’ interests to meet their Sustainable Development Goals, as well as their commitments to the Paris Agreement or other Multilateral Environmental Agreements